PERAN DAN PARTISIPASI POLITIK ORGANISASI NASYIATUL AISYIYAH DALAM MENGINTERNASASIKAN KEBIJAKAN BERPERSPEKTIF GENDER DI KOTAPALEMBANG TAHUN 2016 - Amaliatulwalidain Amaliatulwalidain (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
This research focuses on the role and political participation of Nasyiatul Aisyiyah organization in internalizing gender perspective policy as a reference for local government in formulating a gender responsive regional regulation in Palembang City. This research was conducted at provincial Nasyiatul Aisyiyah Organization (PWNA), city level, to the level of twig that existed all sub-district in Palembang city. Theories and Concepts used in answering research questions using Role theory, and Political Participation, while the method in this study, using qualitative analytical research methods using primary data types obtained directly from the object of research by spreading research questions to informants consisting of all The administrators of the Nasyiatul Aisyiyah Organization from the regional / provincial (PWNA), regional / city (PDNA) levels, to the sub-district / branch level (PRNA). From the research, it was found that the role of political participation of Nasyiatul Aisyiyah organization in internalizing the gender perspective policy in Palembang City, firstly done through internal organization program such as Family Learning Center with institutional strengthening and cadre, in order to have capacity in responding the problem Women as part of public policy. Extradition programs that have been carried out are cooperation and MOU with BNN in handling Drug hazard, and also held an auditor with Child and Women Protection Agency of South Sumatera Province in providing Lactation Room in several public places.Keywords : Role, Political Participation, Nasyiatul Aisyiyah, Gendered Perspectives Policy